Direct harms and social consequences: an analysis of the impact of maternal imprisonment on dependent children in England and Wales - Minson, Shona (Criminology & criminal justice, 2019)
This article draws upon research with children whose mothers were imprisoned in England and Wales, to investigate the impacts of maternal imprisonment on dependent children. The research directly engaged with children, in accordance with Article 12 of the UNCRC 1989, and is set within an examination of the differentiated treatment in the family and criminal courts of England and Wales of children facing state initiated separation from a parent. The article explores children’s ‘confounding grief’ and contends that this grief originates from social processes, experienced as a consequence of maternal imprisonment. ‘Secondary prisonization’ is characterized by changes in home and caregiver and the regulation of the mother and child relationship. ‘Secondary stigmatization’ occurs when children are stigmatized by virtue of their relationship with their mother. These harms to children call into question the state’s fulfilment of its duty to protect children under Article 2 of the UNCRC 1989.